Dampak Radiasi Radioaktif Terhadap Kesehatan - Muhlis Malaka (IAIN Ternate, 2019)
Radioactive elements or radionuclides in the environment can be grouped into two big categories, namely natural radionuclides and artificial radionuclides that both can serve as a source of radiation nature or environment. Source radiation source nice neighborhood the physical and fabrications can serve as a source of radiation on the human body. Radiation received the human body can come from sunber and external internal. An external source is the source of radiation lying outside the human body, while internal resources are a source of radiation inside the human body.